H-1 parvovirus-associated replication bodies: a distinct virus-induced nuclear structure - Cziepluch, Celina; Lichter, Peter; Rommelaere, Jean (Journal of virology, 2000)
We have identified a nuclear structure that is induced after infection with the autonomous parvovirus H-1. Using fluorescence microscopy, we observed that the major nonstructural protein (NS1) of H-1 virus which is essential for viral DNA amplification colocalized with virus-specific DNA sequences and sites of ongoing viral DNA replication in distinct nuclear bodies which we designated H-1 parvovirus-associated replication bodies (H-1 PAR-bodies). In addition, two cellular proteins were shown to accumulate in H1 PAR-bodies: (i) the proliferating cell nuclear antigen (PCNA) which is essential for chromosomal and parvoviral replication and (ii) the NS1-interacting small glutamine-rich TPR-containing protein (SGT), suggesting a role for the latter in parvoviral replication and/or gene expression. Since many DNA viruses target preexisting nuclear structures, known as PML-bodies, for viral replication and gene expression, we have determined the localization of H-1 PAR- and PML-bodies by double-fluorescence labeling and confocal microscopy and found them to be spatially unrelated. Furthermore, H-1 PAR-bodies did not colocalize with other prominent nuclear structures such as nucleoli, coiled bodies, and speckled domains. Electron microscopy analysis revealed that NS1, as detected by indirect immunogold labeling, was localized in ring-shaped electron-dense nuclear structures corresponding in size and frequency to H-1 PAR-bodies. These structures were also clearly visible without immunogold labeling and could be detected only in infected cells. Our results suggest that H-1 virus does not target known nuclear bodies for DNA replication but rather induces the formation of a novel structure in the nucleus of infected cells.
Gesehen am 15.02.2021